VD_FINDINFO HC / 2020 / 443 vom 19. August 2020 - VD Tribunal cantonal (2020)
LOYER ABUSIF, LOYER INITIAL, RENDEMENT NET, LOYER USUEL, FORMULE OFFICIELLE, DÉFAUT DE LA CHOSE | 256 al. 1 CO, 259d CO, 269 CO, 269a CO, 270 CO